1990
DOI: 10.1007/bf01735178
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline poisoning—a review of 64 cases

Abstract: Sixty-four cases of theophylline poisoning were reviewed. All but two cases represented international self poisoning. The majority of patients were young females who presented acutely after ingestion of sustained release preparations prescribed for asthma. Serum theophylline levels (mean 365 mumol/l, SD 177) indicated a high risk of toxicity. Electrolyte and metabolic abnormalities (hypokalaemia, hypomagnesaemia, hypophosphataemia, hyperglycaemia, acid-base disturbances and leucocytosis) were common. Serum pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sessler et al reported that the rate of hyperglycaemia in theophylline toxicities was 62% in their study (3). In other studies, hyperglycaemia rates were found to be 72%, 89% and 93%, respectively (4,11,12). Additionally, in the study of Shannon et al, the mean blood glucose level was 180 mg/dL for theophylline poisoning cases.…”
Section: Discussionmentioning
confidence: 90%
“…Sessler et al reported that the rate of hyperglycaemia in theophylline toxicities was 62% in their study (3). In other studies, hyperglycaemia rates were found to be 72%, 89% and 93%, respectively (4,11,12). Additionally, in the study of Shannon et al, the mean blood glucose level was 180 mg/dL for theophylline poisoning cases.…”
Section: Discussionmentioning
confidence: 90%
“…Hyperglycemia is a frequent finding in theophylline poisoning 5,12 . Some studies have also reported that hyperglycemia has a high prevalence of poisoning 7,11,13,14 . Shannon et al reported the age distribution of theophylline poisoning in the range of 3 months to 98 years with a mean age of 34.5 years 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac manifestations include dysrhythmias, hypotension, and cardiac arrest. Neurological manifestations include: tremors, convulsions, restlessness and headache 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…We described a case of attempted suicide and acute theophylline toxicity. Parr et al (4) reported 64 cases of acute theophylline toxicity, who were all but two Accepted on 13 December 2002 attempted suicide cases.Other causes of acute theophylline toxicity include prescription of high doses by physicians and accidental ingestion. Thus, prescription of theophylline should be accompanied by education of patients and/or their families about the potential dangers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the ¢rst case of successful treatment of acute theophylline toxicity by endoscopy.The reason that STCs can remain high is continued absorption of theophylline as it is released from the sustained-release tablet, throughout the digestive tract. Sustained-release theophylline could remain in the stomach for 8^12 h in acute overdose (4). For example, Macdonald et al reported a case whose STC was 138 mg/ml after 36 h later of 50'Phyllocontin'tablets (aminophylline, 225 mg slow release) ingestion (5).…”
Section: Discussionmentioning
confidence: 99%